Strategi Ekspansi Shopee di Indonesia: Respon dan Kebijakan Indonesia dalam Perspektif Ekonomi Politik Internasional - Lutfiyah Al Humairah (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2025)
Shopee, a Singapore-based e-commerce company, has shown an aggressive and well-planned expansion strategy across Southeast Asia, particularly in Indonesia. Its growth has not only transformed the way people engage in digital transactions but has also introduced new challenges regarding economic security and national digital sovereignty. Shopee’s dominance in the local market reflects regulatory gaps in protecting domestic businesses, as well as the limited government oversight of foreign digital platforms. This paper explores Shopee’s expansion strategy, targeted market segments, and the Indonesian government’s policy responses. Using the international political economy approach and the lens of non-traditional security, this research aims to examine how the presence of foreign platforms like Shopee can influence domestic regulations and generate strategic challenges for national sectors.